STUDY PROCESS OF WASTEWATER TREATMENT IN ANAEROBIC BIOREACTORS - and (Municipal economy of cities (Technical science), 2013)
We describe the main lines of research of the processes occurring in an anaerobic bioreactor for wastewater treatment, and the scheme of the pilot plant anaerobic biofilter.